Hormonal modulation, mitochondria and Alzheimer’s prevention: the role of GLP-1 agonists and estrogens - Lizcano, Fernando; Sanabria, Daniela; Aviles, Eliana (Frontiers in Molecular Biosciences, 2025)
Alzheimer’s disease (AD) is the most prevalent cause of dementia worldwide, disproportionately affecting women and lacking effective disease-modifying therapies. While traditional approaches have focused on amyloid β (Aβ) plaques and tau pathology, emerging evidence highlights the role of metabolic dysfunction, mitochondrial impairment, and hormonal signaling in the pathogenesis of AD. Estrogens exert neuroprotective effects by modulating synaptic plasticity, enhancing mitochondrial bioenergetics, and reducing oxidative stress and inflammation. Similarly, glucagon-like peptide-1 receptor agonists (GLP-1RAs), initially developed for the treatment of type 2 diabetes, have demonstrated promising cognitive benefits, potentially mediated through improved insulin signaling, neuronal survival, and reduced β-amyloid (Aβ) and tau burden. This review explores the converging mechanisms through which estrogens and GLP-1RAs may act synergistically to prevent or delay the onset of AD. We examine the influence of sex differences in mitochondrial dynamics, estrogen receptor distribution, and GLP-1 signaling pathways, particularly within central nervous system regions implicated in AD. Preclinical studies using GLP-1-estrogen conjugates have shown enhanced metabolic and neuroprotective outcomes, accompanied by reduced systemic hormonal exposure, suggesting a viable therapeutic strategy. As the global prevalence of AD continues to rise, especially among postmenopausal women, dual agonism targeting estrogen and GLP-1 receptors may represent a novel, physiologically informed approach to prevention and intervention. Ongoing clinical trials and future research must consider sex-specific factors, receptor polymorphisms, and brain-region selectivity to optimize the translational potential of this combined strategy.